Screening for antioxidant activity, toxicity and anti-diabetic effect of erythroxylum cuneatum standardized aqueous extract / Roslina Ali - Ali, Roslina (2016)
Erythroxylum cuneatum (Erythroxylaceae) standardized aqueous extract was investigated for its antioxidant and antihyperglycemic activities for its safety in vivo. Dried extract was provided by Forest Research Institute of Malaysia (FRIM). Antioxidant activity was evaluated via total phenolic content assay, 1, 1 -diphenyl-2- picrylhydrazyl (DPPH) scavenging activity assay, ferric reducing antioxidant power (FRAP) assay, and via inhibitory effect of extract against lipid peroxidation in liver microsomes induced by tert-butylhydroperoxide (tert-BOOH). Safety of extract was determined using Organization for Economic Co-operation and Development (OECD) guidelines acutely and subacutely in mice. Total phenolic content of extract was 0.38 ±0.15 mg gallic acid equivalent (GAE)/mg dry weight of extract. DPPH assay showed E. cuneatum extract had an EC₅₀ of 6.17 ± 0.02 μg/mL, while the antioxidant references were trolox, gallic acid and quercetin which elicited EC50 values of 3.89 ± 0.09, 0.3 ± 0.07 and 2.69 ± 0.07 μg/mL, respectively. EC50 values for E. cuneatum extract, trolox and gallic acid in the FRAP assay were 3.72 ± 0.28, 12.09 ± 0.44 and 18.59 ± 0.21 (μmol Fe²⁺/ mg dry weight, respectively. IC50 value for E. cuneatum extract, trolox and gallic acid for inhibition of tert-BOOH-induced lipid peroxidation were 31.62 ± 0.10, 10.00 ± 0.21 and 12.59 ±0.12 mg/mL, respectively. Antioxidant activity of extract was correlated to total phenolic content. Based on Organization for Economic Co-operation and Development (OECD) guidelines, oral E. cuneatum extract is non-toxic as no adverse effect were seen at levels of more than 5 g/kg following acute oral administration and 1 g/kg following subacute administration in male and female mice. However, when administered acutely via intraperitoneal route, a dose of 300 mg/kg extract was moderately toxic, thus was harmful. In the streptozotocin induced hyperglycemic rat model, E. cuneatum extract (100 and 300 mg/kg, p.o.) administered twice daily elicited a significant decrease in serum glucose level after 3 weeks of treatment. In summary, E. cuneatum standardized aqueous extract given orally was safe in acute and subacute treatment. It has glucose-lowering effect in hyperglycaemic condition and showed high antioxidant activities in four different antioxidant assays.